Meta Analysis the Effect of Gestational Diabetes Mellitus on Macrosomia and Sectio Caesarea - Ratna, Tantri Yunita; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Gestational Diabetes Mellitus (GDM) is the degree of glucose intolerance that occurs during pregnancy. DMG is caused by damage to cells and insulin resistance, resulting in hyperglycemia and an increase in abnormal growth/macrosomia which causes cesarean delivery. This study aims to analyze the magnitude of the effect of DMG on the incidence of macrosomia and caesarean section with a meta-analysis study. Subjects and Method: This research is a systematic review and meta-analysis conducted using PRISMA flow diagram. Article searches were conducted through journal databases including: PubMed, Science Direct, and Google Scholar by selecting articles published in 2000-2020. The keywords used were: